UKRAINE AND THE EU: INSTITUTIONAL ADAPTATION ON THE PATH TO MEMBERSHIP – LEGAL, ECONOMIC, AND SECURITY DIMENSIONS - Savych, Vita; Pugachov, Volodymyr; Kebko, Volodymyr (Public Management and Policy, 2025)
The article examines Ukraine’s institutional adaptation on its path toward membership in the European Union under the conditions of a full-scale war and the transformation of the EU’s enlargement policy. The introductory section substantiates the relevance of the study, driven by the transformation of European integration into an existential security dimension for both Ukraine and the EU itself, and formulates the aim of the article – to conceptualize institutional adaptation as a polystructurality process that integrates legal, economic, and security dimensions. The empirical basis of the research consists of key EU and Ukrainian documents (conclusions and reports of the European Commission, the Association Agreement, the Strategic Compass, the EU founding treaties, the Constitution of Ukraine, and basic legislation in the field of national security), as well as contemporary academic and analytical works addressing the transformation of enlargement policy and the Ukrainian case. The results section demonstrates that, in the legal dimension, adaptation unfolds under the dual pressure of martial law and the requirements of the rule of law; in the economic dimension, candidate status combines the prospect of deeper integration into the internal market with an unprecedented dependence on external financing; in the security dimension, Ukraine’s de facto inclusion in the European security architecture precedes formal membership, conferring upon enlargement the character of a mechanism of collective survival. The discussion emphasizes that Ukraine’s institutional adaptation is acquiring the features of a “crisis-driven” model, in which decisions in one sphere inevitably entail consequences for others, while the EU is transforming from a mere “exporter of norms” into a co-participant in domestic reforms. The conclusions underline that the Ukrainian experience simultaneously exposes the risks of adaptation formalism and opens up the possibility of rethinking EU enlargement policy as a bilateral process in which Ukraine not only adapts to the Union but also stimulates its internal institutional and geopolitical evolution.